Financial cryptography : 6th International Conference, FC 2002 Southampton, Bermuda, March 11-14, 2002 : revised papers - International conference Financial cryptography, (6th : 2002 : Southamton, Bermuda Islands); Blaze, Matt (New York, NY : Springer-Verlag, 2003)
36